A coupling technique based on method of line and group preserving scheme for solving the nonlinear wave equation. Issue 3 (3rd April 2021) - Partohaghighi, Mohammad; Hesameddini, Esmail; Inc, Mustafa
Abstract: In this work, a powerful approach is presented to solve the nonlinear wave equation (NWE): utt ( x, t ) − u ( x, t ) uxx ( x, t ) = g ( x, t ), where c is a positive constant. Firstly, a discretization is implemented on the original equation. Then, a geometric technique is applied to obtain the approximate solutions. Some examples are displayed to prove the power and capability of the offered approach to work out the wave problem.